Method for reversibly crosslinking compositions

By mixing polar ethylene polymers, free radical initiators and BiTEMPS methacrylates under low temperature conditions, the crosslinkable polymer composition is solved, and the reusability and environmentally friendly sustainability of the material are achieved.

CN119522241APending Publication Date: 2025-02-25DOW GLOBAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052939.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Crosslinked ethylene polymers cannot be processed and/or recycled due to the existence of a permanent crosslinking network, resulting in environmental and sustainability problems.

Method used

A crosslinkable polymer composition is formed by mixing a polar ethylene polymer, a free radical initiator and 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate) under conditions lower than the decomposition temperature of the free radical initiator.

Benefits of technology

Reprocessing and recycling of ethylene polymers has been achieved, reducing environmental pollution and resource waste, and improving the sustainability of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235521260000121
    Figure BDA0005235521260000121
  • Figure BDA0005235521260000151
    Figure BDA0005235521260000151
  • Figure BDA0005235521260000181
    Figure BDA0005235521260000181
Patent Text Reader

Abstract

The present disclosure provides a method. In one embodiment, the method includes feeding a component into a mixing device. The present invention relates to a composition comprising (i) a (polar) ethylene-based polymer having a melting temperature Tm, (ii) a free-radical initiator having a decomposition temperature Tdecomposition, and (iii) a 2, 2, 6, 6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate), and to a method for producing the same, the composition comprising: (i) a (polar) ethylene-based polymer having a melting temperature Tm, (ii) a free-radical initiator having a decomposition temperature Tdecomposition, and (iii) a 2, 2, 6, 6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The method comprises mixing component (i), component (ii) and component (iii) in the mixing device at a temperature lower than the decomposition temperature of the radical initiator. The method includes forming a crosslinkable polymer composition comprising the (polar) ethylene-based polymer, the BITEMPS methacrylate, and the free radical initiator.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Crosslinked olefin polymers, particularly crosslinked ethylene polymers, are well known for their excellent mechanical properties, high thermal stability, and outstanding chemical resistance in numerous applications. Unfortunately, crosslinked ethylene polymers, also known as thermoset polymers, cannot be reprocessed and / or recycled due to the presence of a permanent crosslinking network within the ethylene polymer. Thus, the use of crosslinked ethylene polymers brings with it attendant environmental and sustainability issues.

[0002] The ability to reprocess and / or recycle crosslinked ethylene polymers has been a long-standing challenge. Accordingly, the art recognizes a need for crosslinked olefin polymers (and particularly crosslinked ethylene polymers) that can be reprocessed and / or recycled. Summary of the invention

[0003] The present disclosure provides a method. In one embodiment, the method includes feeding components into a mixing device. The components include (i) a (polar) ethylene polymer having a melting temperature Tm, (ii) a free radical initiator having a decomposition temperature Tm, 分解 , and (iii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The method comprises mixing component (i), component (ii) and component (iii) in the mixing device at a temperature below the decomposition temperature of the free radical initiator. The method comprises forming a crosslinkable polymer composition, the crosslinkable polymer composition comprising the (polar) vinyl polymer, the BiTEMPS methacrylate and the free radical initiator.

[0004] definition

[0005] All references to the Periodic Table of the Elements herein shall refer to the Periodic Table of the Elements published and copyrighted by CRC Press, Inc. in 2003. Furthermore, any reference to one or more groups shall be to the one or more groups reflected in such Periodic Table of the Elements using the IUPAC system for numbering groups. Unless stated to the contrary, implied by the context, or customary in the art, all parts and percentages are by weight. For purposes of U.S. patent practice, any patent, patent application, or publication referred to herein is incorporated herein by reference in its entirety (or its equivalent U.S. version is so incorporated by reference).

[0006] The numerical range disclosed herein includes all values ​​from the lower limit to the upper limit and including the lower limit and the upper limit. For a range containing clear values ​​(e.g., a range of 1 or 2, or 3 to 5, or 6, or 7), any sub-range between any two clear values ​​is included (e.g., the above range 1 to 7 includes 1 to 2; 2 to 6; 5 to 7; 3 to 7; 5 to 6; etc.).

[0007] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.

[0008] The term "composition" as used herein refers to a mixture of materials which comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0009] The term "comprising" and its derivatives are not intended to exclude the presence of any additional components, steps or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequent listing any other components, steps or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step or procedure not specifically recited or listed.

[0010] "Ethylene polymers" are polymers containing more than 50 mol% of polymerized ethylene monomers (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Ethylene polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene polymers" and "polyethylene" are used interchangeably. Non-limiting examples of ethylene polymers (polyethylene) include low density polyethylene (LDPE) and linear polyethylene. Non-limiting examples of linear polyethylene include linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), ethylene / alpha-olefin multi-block copolymers (also known as olefin block copolymers (OBC)), substantially linear or linear plastomers / elastomers, and high density polyethylene (HDPE). Generally speaking, polyethylene can be produced in a gas phase fluidized bed reactor, a liquid phase slurry reactor or a liquid phase solution reactor using a heterogeneous catalyst system (such as a Ziegler-Natta catalyst), a homogeneous catalyst system comprising a Group 4 transition metal and a ligand structure (such as a metallocene, a non-metallocene metal center, a heteroaryl, an isovalent aryloxy ether, a phosphinimine, etc.). Combinations of heterogeneous and / or homogeneous catalysts can also be used in a single reactor or multiple reactor configurations.

[0011] An "ethylene plastomer / elastomer" is a substantially linear or linear ethylene / α-olefin interpolymer containing a homogeneous distribution of short chain branches, the ethylene / α-olefin interpolymer comprising units derived from ethylene and units derived from at least one C3-C 10 The ethylene plastomers / elastomers have a density of 0.854 g / cc to 0.920 g / cc. Non-limiting examples of ethylene plastomers / elastomers include AFFINITY TM Polyolefin plastomers and ENGAGE TM Polyolefin elastomer (available from The Dow Chemical Company), EXACT TM Plastomers (available from ExxonMobil Chemical), Tafmer TM α-olefin copolymer (available from Mitsui), Solumer TM Polyolefin Elastomers and Supreme TM Polyolefin plastomers (available from SK Chemicals Co.) and Lucene TM Polyolefin plastomer (available from LG Chem Ltd.).

[0012] "High density polyethylene" (or "HDPE") is a homopolymer of ethylene or ethylene with at least one C4-C10 The HDPE may be a unimodal copolymer or a multimodal copolymer. A "unimodal ethylene copolymer" is an ethylene / α-olefin copolymer having one distinct peak in a gel permeation chromatography (GPC) showing a molecular weight distribution. 10 α-olefin copolymers. "Multimodal ethylene copolymers" are ethylene / C4-C6 copolymers having at least two distinct peaks in a GPC graph showing molecular weight distribution. 10 α-olefin copolymers. Multimodal includes copolymers with two peaks (bimodal) and copolymers with more than two peaks. Non-limiting examples of HDPE include DOW TM High-density polyethylene (HDPE) resin (available from The Dow Chemical Company), ELITE TM Enhanced polyethylene resin (available from The Dow Chemical Company), CONTINUUM TM Bimodal polyethylene resin (available from The Dow Chemical Company), LUPOLEN TM (available from LyondellBasell) and HDPE products from Borealis, Ineos and ExxonMobil.

[0013] As used herein, the term "linear low density polyethylene" (or "LLDPE") refers to a linear ethylene / α-olefin copolymer containing a heterogeneous distribution of short chain branches, which comprises units derived from ethylene and units derived from at least one C3-C 10 Units of α-olefins or C4-C8 α-olefin comonomers. LLDPE is characterized by minimal long chain branching (if any) compared to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN TM Linear low density polyethylene resin (available from The Dow Chemical Company), DOWLEX TM Polyethylene resin (available from The Dow Chemical Company) and MARLEX TM Polyethylene (available from Chevron Phillips).

[0014] The term "low density polyethylene" (or "LDPE") may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene" and is an ethylene homopolymer and is typically produced by high pressure free radical polymerization (≥100 MPa (e.g., 100 MPa to 400 MPa), tubular reactor or autoclave reactor with a free radical initiator). The density of LDPE resins is typically in the range of 0.915 g / cc to less than 0.940 g / cc. LDPE is distinct from LLDPE.

[0015] As used herein, "olefin polymer" or "polyolefin" is a polymer containing more than 50 mole % polymerized olefin monomer (based on the total amount of polymerizable monomers) and optionally may contain at least one comonomer. Non-limiting examples of olefin polymers include ethylene-based polymers and propylene-based polymers.

[0016] "Polymer" is a compound prepared by polymerizing monomers of the same or different types that provide multiple and / or repeating "units" or "monomer units" constituting the polymer in a polymerized form. Therefore, the general term polymer covers the term homopolymer, which is usually used to refer to polymers prepared from only one type of monomer, and the term copolymer, which is usually used to refer to polymers prepared from at least two types of monomers. The general term also covers all forms of copolymers, such as random copolymers, block copolymers, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" represent copolymers prepared by polymerizing ethylene or propylene and one or more other polymerizable α-olefin monomers, respectively, as described above. It should be noted that although polymers are often referred to as being "made of" one or more specific monomers, "based on" a specific monomer or monomer type, "containing" a specific monomer content, etc., in this context, the term "monomer" should be understood to refer to the polymerized remains of a specific monomer, rather than an unpolymerized species. In general, polymers herein refer to "units" based on the polymerized form of the corresponding monomer.

[0017] Test Method

[0018] Compression molded samples Form at 180°C and 10 MPa molding pressure for 5 minutes and then quench between cooling platens (15-20°C) for 2 minutes, or as otherwise described herein.

[0019] Compression Set (C-Set) Measurement Compression set was measured according to ASTM Method 395, Method B, using the following conditions: a 1-inch diameter approximately 0.5-inch (t 初始) thickness disks were pressed to a thickness of 0.375 inches and aged at 70°C and 100°C for 20 hours; thereafter, the samples were released and allowed to stand at room temperature for 30 minutes, and then the thickness t was measured again. 最终 The compression set (C-set) is calculated using the following equation: C-set = (t 初始 -t 最终 ) / (t 初始 -0.375)*100%. The reported C-set is the average of 3 repeated measurements.

[0020] density Measured according to ASTM D792, with results reported in g / cc at 25°C.

[0021] Dynamic Mechanical Analysis (DMA) DMA experiments were performed using a TA Instruments RSA-G2 solid analyzer to measure the storage modulus (G'), loss modulus (G"), and damping ratio (tan δ) of the networks as a function of temperature and recovery under a nitrogen atmosphere. The DMA was operated in tension mode with a frequency of 1 Hz and an oscillating strain of 0.03%. Data were collected from room temperature to 160 °C at a heating rate of 3 °C / min.

[0022] Measured using ASTM D648 method Heat Deflection Temperature (HDT) The temperatures at which the samples deformed under loads of 0.455 MPa and 1.82 MPa are reported.

[0023] Melt Index (MI or I2) (for ethylene polymers) is measured according to ASTM D 1238, Condition 190°C / 2.16 kg, where the results are reported in grams per 10 minutes (g / 10 min). 21 Measured according to ASTM D 1238, Condition 190°C / 21.6 kg, where the results are reported in grams per 10 minutes (g / 10 min).

[0024] Rheological analysisUse rubber processing analyzer (RPA) to carry out.Use rotorless oscillating shear rheometer AlphaTechnologies RPA 2000 instrument, according to ASTM D6204, measure the rheology of composition under the following test conditions and exceptions.Sample is placed between two polyester films for analysis.Rheology is monitored at 180 ℃, 1.0rad / s, 7% strain for 60 minutes during initial timing test.Record the elastic torque S' at the end of 60 minutes (min) crosslinking step.After 60 minutes at 160 ℃, immediately at 180 ℃, 7% strain, the same sample is subjected to a frequency sweep of 0.1rad / s to 300rad / s, then at 190 ℃, 7% strain, a frequency sweep of 0.1rad / s to 300rad / s, and then at 230 ℃, 7% strain, a frequency sweep of 0.1rad / s to 300rad / s.Record the dynamic complex viscosity, n* and tanδ of each frequency sweep. In ASTM D6204, a frequency sweep is performed on unvulcanized rubber before the curing step. In this case, a frequency sweep is performed at 180°C after the initial crosslinking step to evaluate the reversibility of the crosslinking. The viscosity-temperature reprocessing ratio (or "VRR") is defined as follows:

[0025] VRR is the ratio of n* at 0.1 rad / s and 180°C to n* at 0.1 rad / s and 230°C.

[0026] Tensile measurement at 80°C . Tensile measurements were performed on an INSTRON device at a tensile speed of 1 inch / minute according to the ASTM D1708 standard. Tensile bars were prepared by punching out from a compression molded sheet with a thickness of 1.5 mm. The test was carried out in an environmental chamber where the temperature was equilibrated at 80°C for 30 minutes before testing. Here, the tensile strength is recorded to reflect whether the material has cross-linked properties, which is the maximum stress applied before the sample breaks. These parameters are averaged over 3 repeated tensile measurements. The cross-linked portion generally has a significantly higher tensile strength at break than the non-cross-linked portion.

[0027] Thermomechanical analysis (Penetration Temperature) was conducted on 30 mm diameter x 3.3 mm thick compression molded discs, formed at 180°C and 10 MPa molding pressure for 5 minutes, and then air quenched. The instrument used was a TA Instruments TMA400, a thermomechanical analyzer. In the test, a 1.5 mm probe was applied to the surface of the sample disc with a force of 1 N. The temperature was increased from 25°C at 5°C / min. Probe penetration was measured as a function of temperature. The experiment ended when the probe penetrated into the sample at 1000 mm (1 mm).

[0028] Vicat softening pointMeasured using ASTM D 1525. Report the temperature when a flat-tip needle penetrates the sample to 1 mm thickness at a load of 10 N. DETAILED DESCRIPTION

[0029] The present disclosure provides a method. In one embodiment, the method includes feeding components into a mixing device. The components include (i) a (polar) ethylene polymer having a melting temperature Tm, (ii) a free radical initiator having a decomposition temperature Tm, 分解 , and (iii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The method comprises mixing component (i), component (ii) and component (iii) in the mixing device at a temperature below the decomposition temperature of the free radical initiator. The method comprises forming a crosslinkable polymer composition, the crosslinkable polymer composition comprising the (polar) vinyl polymer, the BiTEMPS methacrylate and the free radical initiator.

[0030] A. (Polar) Ethylene Polymers

[0031] Component comprises (polar) ethylene polymer.As used herein, "(polar) ethylene polymer" is (i) polar ethylene polymer, (ii) ethylene polymer, or (iii) the combination of (i) and (ii).As used herein, "polar ethylene polymer" is the ethylene polymer consisting of (i) ethylene monomer, (ii) comonomer containing heteroatoms and (iii) optional terionomer (which may or may not contain heteroatoms).In other words, polar ethylene polymer is not hydrocarbon.The melt index (MI) of polar ethylene polymer is 0.1g / 10min to 100g / 10min, or 1g / 10min to 100g / 10min, or 1g / 10min to 50g / 10min, or 1g / 10min to 25g / 10min, or 1g / 10min to 10g / 10min, or 1g / 10min to 5g / 10min. Non-limiting examples of comonomers having heteroatoms include carbon monoxide, carboxylic acids, esters, alkyl acrylates having 1 to 30 carbon atoms, methacrylates having 1 to 30 carbon atoms, vinyl siloxanes having 1 to 16 carbon atoms, and halogens. Non-limiting examples of suitable polar vinyl polymers include ethylene / carboxylic acid copolymers and ionomers partially neutralized with metal salts derived therefrom, ethylene / acrylic acid copolymers (EAA), ethylene / methacrylic acid copolymers (EMAA), ethylene / vinyl (trimethoxy) silane copolymers (EVTMS), ethylene / vinyl acetate copolymers (EVA), ethylene / methyl acrylate (EMA), ethylene / ethyl acrylate copolymers (EEA), ethylene / butyl acrylate copolymers (EBA), ethylene / carbon monoxide (ECO), ethylene / glycidyl methacrylate (E / GMA), ethylene / methyl methacrylate copolymers, ethylene / butyl methacrylate copolymers, ethylene / stearyl acrylate copolymers, ethylene / stearyl methacrylate copolymers, ethylene / octyl acrylate copolymers, ethylene / 2-ethylhexyl acrylate copolymers, ethylene / dodecyl acrylate copolymers, polyvinyl dichloride (PVCD), ethylene / maleic anhydride copolymers (EMAH), polyvinyl chloride (PVC), and combinations thereof.Additional non-limiting examples of terpolymers include ethylene / carboxylic acid / acrylate terpolymers and partially neutralized ionomers with metal salts derived therefrom, ethylene / methyl acrylate / vinyl (trimethoxy) silane terpolymers (EMAVTMS), ethylene / ethyl acrylate / vinyl (trimethoxy) silane terpolymers (EEAVTMS), ethylene / butyl acrylate / vinyl (trimethoxy) silane terpolymers (EBAVTMS), ethylene / methyl acrylate / glycidyl methacrylate (EMAGMA), ethylene / butyl acrylate / glycidyl methacrylate (EBAGMA), ethylene / vinyl acetate / maleic anhydride terpolymers (EEAMAH), ethylene ethyl acrylate / maleic anhydride (EEAMAH) terpolymers, and combinations thereof.

[0032] In one embodiment, the polar vinyl polymer is an ethylene / vinyl acetate copolymer.

[0033] The (polar) ethylene polymer may be an ethylene polymer. As used herein, "ethylene polymer" is a hydrocarbon and is therefore different from a polar ethylene polymer containing heteroatoms. The ethylene polymer may be an ethylene homopolymer, an ethylene / α-olefin interpolymer or an ethylene / C4-C 20 Alpha-olefin copolymers. In embodiments herein, ethylenes include more than 50% by weight of units derived from ethylene and less than 30% by weight of units derived from one or more alpha-olefin comonomers (based on the total amount of polymerizable monomers). All individual values ​​and subranges of units derived from ethylene greater than 50% by weight and less than 30% by weight of units derived from one or more alpha-olefin comonomers. Suitable alpha-olefin comonomers generally have no more than 20 carbon atoms. For example, alpha-olefin comonomers may have 3 to 10 carbon atoms or 3 to 8 carbon atoms. Exemplary alpha-olefin comonomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene and 4-methyl-1-pentene. The one or more α-olefin comonomers may, for example, be selected from the group consisting of propylene, 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of 1-hexene and 1-octene. In some embodiments, the ethylene-based polymer comprises greater than 0 wt % and less than 30 wt % of units derived from one or more of 1-octene, 1-hexene, or 1-butene comonomers.

[0034] The melt index (MI) of the ethylene polymer is 0.1 g / 10min to 100 g / 10min, or 1 g / 10min, to 100 g / 10min, or 1 g / 10min to 50 g / 10min, or 1 g / 10min to 25 g / 10min, or 1 g / 10min to 10 g / 10min, or 1 g / 10min to 5 g / 10min. In embodiments herein, the density of the ethylene polymer is in the range of 0.854 g / cc to 0.925 g / cc. All individual values ​​and subranges of 0.854 g / cc to 0.925 g / cc are included and disclosed herein. In some embodiments, the density of the ethylene composition may be 0.895 g / cc to 0.925 g / cc, 0.900 g / cc to 0.925 g / cc, 0.900 g / cc to 0.920 g / cc, 0.900 g / cc to 0.915 g / cc, 0.900 g / cc to 0.912 g / cc, 0.900 g / cc to 0.911 g / cc, or 0.900 g / cc to 0.910 g / cc. In further specific embodiments, the density of the ethylene polymer composition may be 0.875 g / cc to 0.925 g / cc, 0.890 g / cc to 0.925 g / cc, 0.900 g / cc to 0.925 g / cc, 0.903 g / cc to 0.925 g / cc, or 0.905 g / cc to 0.925 g / cc. Density can be measured according to ASTM D792.

[0035] Non-limiting examples of suitable ethylene-based polymers include ethylene / α-olefin interpolymers, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and combinations thereof.

[0036] In one embodiment, the ethylene / α-olefin interpolymer is an ethylene / C4-C8 α-olefin copolymer having one, some, or all of the following characteristics:

[0037] (i) octene comonomer; and / or

[0038] (ii) a density of 0.860 g / cc to 0.925 g / cc, or 0.880 g / cc to 0.920 g / cc, or 0.899 g / cc to 0.915 g / cc, or 0.899 g / cc to 0.910 g / cc; and / or

[0039] (iii) a melt index of 0.5 g / 10 min to 100 g / 10 min, or 1 g / 10 min to 30 g / 10 min, or 2 g / 10 min to 20 g / 10 min. Suitable ethylene / C 4-Non-limiting examples of C8 alpha-olefin copolymers include ENGAGE TM 8450POE、ENGAGE TM 8402POE、ENGAGE TM 8401POE、ELITE TM 5815 reinforced polyethylene resin, ELITE TM 5220 reinforced polyethylene resin or their blends.

[0040] In one embodiment, the ethylene polymer is an ethylene / α-olefin multi-block copolymer. The term "ethylene / α-olefin multi-block copolymer" refers to an ethylene / C3-C8α-olefin multi-block copolymer composed of ethylene and a copolymerizable C3-C8α-olefin comonomer or C4-C8α-olefin comonomer (and optional additives) in polymerized form, and the polymer is characterized in that multiple blocks or segments of two polymerized monomer units are different in chemical or physical properties, and the blocks are connected (or covalently bonded) in a linear manner, i.e., a polymer containing chemically distinguishable units connected end-to-end relative to the polymerized olefinic functionality. Ethylene / α-olefin multi-block copolymers include block copolymers with two blocks (diblocks) and more than two blocks (multi-blocks). C3-C8α-olefins are selected from propylene, butene, hexene and octene. Ethylene / α-olefin multi-block copolymers do not contain or otherwise do not contain styrene (i.e., do not contain styrene), and / or ethylene aromatic monomers, and / or conjugated dienes. When referring to the amount of "ethylene" or "comonomer" in a copolymer, it is understood that this refers to polymerized units thereof. In some embodiments, the ethylene / α-olefin multi-block copolymer may be represented by the formula: (AB) n ; wherein n is at least 1, preferably an integer greater than 1, such as 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more, "A" represents a hard block or segment and "B" represents a soft block or segment. Preferably, A and B are connected or covalently bonded in a substantially linear manner, or in a linear manner, relative to a substantially branched or substantially star-shaped manner. In other embodiments, the A blocks and B blocks are randomly distributed along the polymer chain. In other words, the block copolymer generally does not have the following structure: AAA-AA-BBB-BB. In one embodiment, the ethylene / α-olefin multi-block copolymer does not have a third type of block, which comprises one or more different comonomers. In another embodiment, block A and block B each have monomers or comonomers that are substantially randomly distributed within the block. In other words, neither block A nor block B comprises two or more subsegments (or subblocks) of different compositions, such as an end segment having a substantially different composition than the remainder of the block.

[0041] In one embodiment, ethylene comprises the majority of the mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene comprises at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene accounts for at least 60% by weight, at least 70% by weight, or at least 80% by weight, and the substantial remainder of the entire ethylene / α-olefin multi-block copolymer comprises C3-C8 α-olefin comonomers or C4-C8 α-olefin comonomers. In one embodiment, the ethylene / α-olefin multi-block copolymer contains 50% to 90% by weight of ethylene, or 60% to 85% by weight of ethylene, or 65% to 80% by weight of ethylene.

[0042] Ethylene / alpha-olefin multi-block copolymers include various amounts of "hard" segments and "soft" segments. "Hard" segments are blocks of polymerized units, wherein based on the weight of the polymer, ethylene is present in an amount greater than 90 wt %, or 95 wt %, or greater than 95 wt %, or greater than 98 wt %, up to 100 wt %. In other words, by the weight of the polymer, the comonomer content (except the monomer content of ethylene) in the hard segments is less than 10 wt %, or 5 wt %, or less than 5 wt %, or less than 2 wt %, and can be as low as zero. In some embodiments, the hard segments include all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units, in which, by the weight of the polymer, the comonomer content (the content of monomers other than ethylene) is greater than 5 wt %, or greater than 8 wt %, greater than 10 wt %, or greater than 15 wt %. In one embodiment, the comonomer content in the soft segments is greater than 20 wt%, greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, or greater than 60 wt% and can be as high as 100 wt%.

[0043] The soft segment can be present in ethylene / alpha-olefin multi-block copolymers from 1% to 99% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer, or from 5% to 95% by weight, 10% to 90% by weight, 15% to 85% by weight, 20% to 80% by weight, 25% to 75% by weight, 30% to 70% by weight, 35% to 65% by weight, 40% to 60% by weight, or 45% to 55% by weight of the total weight of the ethylene / alpha-olefin multi-block copolymer. On the contrary, the hard segment can be present in a similar range. The soft segment weight percentage and the hard segment weight percentage can be calculated based on the data obtained from DSC or NMR. Such methods and calculations are disclosed, for example, in USP 7,608,668, entitled "Ethylene / α-Olefin Block Inter-Polymers", filed on March 15, 2006 in the name of Colin L.P. Shan, Lonnie Hazlitt et al. and assigned to Dow Global Technologies Inc., the disclosure of which is incorporated herein by reference in its entirety. Specifically, the hard segment weight percentage and the soft segment weight percentage and the comonomer content can be determined as described in columns 57 to 63 of USP 7,608,668.

[0044] In addition, the ethylene / α-olefin multi-block copolymer has a PDI (or Mw / Mn) that fits the Schultz-Flory distribution rather than the Poisson distribution. The ethylene / α-olefin multi-block copolymer of the present invention has both a polydisperse block distribution and a polydisperse distribution of block sizes. This results in the formation of a polymer product with improved and distinguishable physical properties. The theoretical benefits of a polydisperse block distribution have been previously described in Potemkin, Physical Review E( Physical Review E ) (1998) 57(6), pp. 6902-6912 and Dobrynin, Journal of Chemical Physics ( J.Chem.Phvs.)》 The theoretical benefits of polydisperse block distributions are modeled and discussed in (1997) 107(21), pp. 9234-9238.

[0045] In one embodiment, the ethylene / α-olefin multi-block copolymers of the present invention have a most probable distribution of block lengths.

[0046] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / 1-octene multi-block copolymer (consisting only of ethylene and octene comonomers) and has one, some, or all of the following properties:

[0047] (i) an Mw / Mn of from 1.7, or 1.8 to 2.2, or 2.5, or 3.5; and / or

[0048] (ii) a density of 0.860 g / cc, or 0.865 g / cc to 0.870 g / cc, or 0.877 g / cc, or 0.880 g / cc; and / or

[0049] (iii) a melting point Tm of 115°C, or 118°C, or 119°C, or 120°C to 120°C, or 123°C, or 125°C; and / or

[0050] (iv) a melt index (MI) of 0.1 g / 10 min, or 0.5 g / 10 min to 1.0 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min; and / or

[0051] (v) 50 to 85 weight percent soft segments and 50 to 15 weight percent hard segments (based on the total weight of the ethylene / octene multi-block copolymer); and / or

[0052] (vi) 10 mol%, or 13 mol%, or 14 mol%, or 15 mol% to 16 mol%, or 17 mol%, or 18 mol%, or 19 mol%, or 20 mol% octene in the soft segments; and / or

[0053] (vii) 0.5 mol%, or 1.0 mol%, or 2.0 mol%, or 3.0 mol% to 4.0 mol%, or 5 mol%, or 6 mol%, or 7 mol%, or 9 mol% of octene in the hard segments; and / or

[0054] (viii) 300% min at 21°C as measured according to ASTM D 1708 ·1 50%, or 60% to 70%, or 80%, or 90% elastic recovery (Re) at deformation rate; and / or

[0055] (ix) Polydispersity distribution of blocks and polydispersity distribution of block sizes (hereinafter referred to as multi-block copolymer properties (i) to (ix)).

[0056] In one embodiment, the ethylene / α-olefin multi-block copolymer is an ethylene / octene multi-block copolymer. The ethylene / octene multi-block copolymer is marketed under the trade name INFUSE TM Olefin block copolymers are commercially available from The Dow Chemical Company, Midland, Michigan, USA.

[0057] Ethylene / α-olefin multi-block copolymers can be produced via a chain shuttling process as described in USP 7,858,706, which is incorporated herein by reference. Specifically, suitable chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Suitable catalysts are described in column 19, line 45 to column 46, line 19 and suitable co-catalysts are described in column 46, line 20 to column 51, line 28. The process is described throughout the literature, but particularly in column 51, line 29 to column 54, line 56. The process is also described, for example, in the following: USP 7,608,668; USP 7,893,166; and USP 7,947,793.

[0058] B. Free Radical Initiators

[0059] The component comprises a free radical initiator. In one embodiment, the free radical initiator is an organic peroxide. Non-limiting examples of suitable organic peroxides include bis(1,1-dimethylethyl)peroxide; bis(1,1-dimethylpropyl)peroxide; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane; 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne; 4,4-bis(1,1-dimethylethylperoxy)pentanoic acid; butyl ester; 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane; benzoyl peroxide; tert-butyl peroxybenzoate; di-tert-amyl peroxide ( "DTAP"); bis(α-tert-butylperoxyisopropyl)benzene ("BIPB"); isopropylcumyl tert-butyl peroxide; tert-butylcumyl peroxide; di-tert-butyl peroxide; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane; 2,5-bis(tert-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane; isopropylcumylcumyl peroxide; butyl 4,4-di(tert-butylperoxy)valerate; di(isopropylcumyl) peroxide; diisopropylbenzene peroxide, and combinations thereof.

[0060] In one embodiment, the free radical initiator is dicumyl peroxide.

[0061] C. BiTEMPS methacrylate disulfide

[0062] The composition comprises 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide, interchangeably referred to as "BiTEMPS methacrylate" or "BiTEMPS" or "BiT." BiTEMPS methacrylate disulfide has the following structure 1.

[0063] Structure 1

[0064]

[0065] D. Blend Components

[0066] In one embodiment, the component comprises a blend component. Non-limiting examples of suitable blend components include polyolefins (e.g., polyethylene other than ethylene polymers crosslinked with BiTEMPS methacrylate and polypropylene), polymers (e.g., polystyrene, ABS, SBS, etc.), and combinations thereof. Non-limiting examples of suitable polyolefins include polyethylene; polypropylene; polybutene (e.g., polybutene-1); polypentene-1; polyhexene-1; polyoctene-1; polydecene-1; poly-3-methylbutene-1; poly-4-methylpentene-1; polyisoprene; polybutadiene; poly-1,5-hexadiene; interpolymers derived from olefins; interpolymers derived from olefins and other polymers such as polyvinyl chloride, polystyrene, polyurethane, etc.; and mixtures thereof.

[0067] E. Additives

[0068] The component may include one or more optional additives. Non-limiting examples of suitable additives include grafting initiators, crosslinking catalysts, blowing agents, blowing agent activators (e.g., zinc oxide, zinc stearate, etc.), auxiliary agents (e.g., triallyl cyanurate), plasticizers, process oils, processing aids, carbon black, colorants or pigments, stability control agents, nucleating agents, fillers, antioxidants, acid scavengers, ultraviolet (UV) stabilizers, flame retardants, lubricants, processing aids, extrusion aids, and combinations thereof. When present, the total amount of additives may be greater than 0% to 80%, or 0.001% to 70%, or 0.01% to 60%, or 0.1% to 50%, or 0.1% to 40%, or 0.1% to 20%, or 0.1% to 10%, or 0.1% to 5% of the total weight of the composition.

[0069] F. Mix

[0070] Components (i) (polar) ethylene polymer, (ii) free radical initiator (peroxide) and (iii) BiTEMPS (and optional additives) are mixed in a mixing device. In one embodiment, the components form a mixture and the mixture comprises

[0071] 70 wt % to 98.5 wt %, or 77 wt % to 98.5 wt % (polar) ethylene polymer;

[0072] 0.1 wt % to 10 wt %, or 0.1 wt % to 5 wt %, 0.1 wt % to 3.0 wt %, or 0.1 wt % to 1.5 wt %, or 0.5 wt % to 1.5 wt % of a free radical initiator which is an organic peroxide such as dicumyl peroxide;

[0073] as well as

[0074] 1 wt % to 20 wt %, or 1 wt % to 15 wt %, or 2 wt % to 20 wt %, or 2 wt % to 10 wt % BiTEMPS methacrylate disulfide. It is understood that the aggregate of (polar) vinylic polymer, free radical initiator and BiTEMPS methacrylate disulfide (and optional additives) totals 100 wt % of the mixture.

[0075] The method comprises mixing components (i), (ii) and (iii) (and optional additives) in a mixing device at a temperature below the decomposition temperature of the free radical initiator (peroxide) to form a crosslinkable polymer composition. The crosslinkable polymer composition comprises (i) (polar) vinyl polymer, (ii) free radical initiator (peroxide) and (iii) BiTEMPS (and optional additives). The method ensures that the mixing temperature (and / or mixing behavior) does not trigger (i.e., does not "start") the free radical initiator. In this way, the resonance peak crosslinkable polymer composition does not contain or otherwise does not contain (i) crosslinking, (ii) grafting and / or (iii) does not contain a combination of (i) and (ii). In other words, the gel content of the crosslinkable polymer composition is 0%, or substantially 0%.

[0076] In one embodiment, an extruder is used to produce the crosslinkable polymer composition in the post-reactor step. The extruder can be a single screw extruder, a multi-screw extruder with positive and negative conveying screw elements, and a lobed kneading / mixing plate, paddle or block.

[0077] In one embodiment, the process comprises mixing at a temperature of greater than or equal to the melting temperature of the (polar) vinylic polymer and less than the decomposition temperature of the free radical initiator.

[0078] In one embodiment, the free radical initiator is dicumyl peroxide, and the process comprises mixing at a temperature below 140°C, or mixing at a temperature from 30°C to below 140°C, or 40°C to below 140°C, or 50°C to below 140°C, or 60°C to below 140°C, or 70°C to below 140°C, or 80°C to below 140°C, or 90°C to below 140°C, or 100°C to below 140°C.

[0079] In one embodiment, the mixing comprises

[0080] (A) melt blending a (polar) ethylene-based polymer at a first temperature for a first process period;

[0081] (B) adding BiTEMPS and a free radical initiator to the melt blended ethylene polymer of step (A) during a second process period to form a mixture;

[0082] (C) blending the mixture; and

[0083] (D) forming a crosslinkable polymer composition.

[0084] The (polar) ethylene polymer is melt blended in a first period of time. In one embodiment, the first temperature of process step (A) is the T of the (polar) ethylene polymer. m The first temperature is sufficient to cause complete or substantially complete melting of the (polar) ethylene polymer. The first temperature is below the decomposition temperature of the free radical initiator.

[0085] In one embodiment, the free radical initiator is dicumyl peroxide and the first temperature is a temperature of 60°C to less than 140°C, or 80°C to less than 140°C, or 85°C to 135°C, or 85°C to 130°C, or 90°C to 120°C. In a further embodiment, the first temperature is greater than or equal to the Tm of the (polar) ethylene polymer to less than the Tm of the free radical initiator. 分解 temperature.

[0086] In the second period, BiTEMPS and a free radical initiator are added and mixed into the molten (polar) ethylene polymer. In one embodiment, the first process period ends before the second process period begins.

[0087] In step (C), the mixing temperature is maintained below the decomposition temperature of the free radical initiator. The free radical initiator does not initiate (ie, does not "start").

[0088] In one embodiment, steps (A) to (D) are carried out in an extruder. Alternatively, steps (A) to (D) are carried out in a batch mixing device (such as a Haake TM mixing device).

[0089] The process forms (D) a crosslinkable polymer composition.

[0090] In one embodiment, the method includes collecting the crosslinkable polymer composition.The crosslinkable polymer composition can be collected or otherwise formed as a plurality of pellets, as one or more bags, or as a combination of pellets and bags.

[0091] The extruder can be operated at a production rate sufficient to produce greater than or equal to 2,000 pounds of the crosslinkable polymer composition per hour, or greater than or equal to 2,100 pounds of the crosslinkable polymer composition per hour, or greater than or equal to 2,200 pounds of the crosslinkable polymer composition per hour.

[0092] The screw speed may be between 200 rpm and 900 rpm. The screw speed is adjusted based on the torque produced and the melt temperature. The barrel temperature in the reaction zone of the extruder may be between 60°C and less than 140°C.

[0093] G. Cross-linking

[0094] In one embodiment, the method comprises heating a crosslinkable polymer composition to a crosslinking temperature of 160°C to less than 199°C, or 180°C to less than 199°C, forming the crosslinkable polymer composition into a preform at the crosslinking temperature; cooling the preform to below the crosslinking temperature; and forming a crosslinked article. In a further embodiment, the crosslinked article comprises (i) a (polar) vinyl polymer and a bond having structure 2 formed from 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate). The crosslinked article contains a disulfide bond formed from BiTEMPS methacrylate by a crosslinking reaction, the disulfide bond having the following structure 2.

[0095] Structure 2

[0096]

[0097] The term (and structure) "P" in Structure 2 above refers to the chains of polymerized (polar) ethylene (and optional comonomers) of the (polar) ethylene polymer. The ethylene polymer of the crosslinked composition can be any ethylene polymer having a MI of 0.1 g / 10 min to 100 g / 10 min as previously disclosed herein.

[0098] In one embodiment, the forming step is a procedure selected from the group consisting of injection molding, extrusion molding, thermoforming, blow molding, overmolding, insert molding, blow molding, casting, tentering, compression molding, and combinations thereof.

[0099] Non-limiting examples of suitable articles for the crosslinked (polar) ethylene polymer compositions having bonds of Structure 2 formed from BiTEMPS methacrylate include elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weatherstripping; lid linings; flooring; and combinations thereof.

[0100] H. Reprocessing

[0101] BiTEMPS methacrylate is a "dynamic crosslinker." The dynamic crosslinker BiTEMPS methacrylate enables the formation of a crosslinked network of ethylene polymers through disulfide bonds between chains of the ethylene polymer. The crosslinked network is formed by the ethylene polymer and BiTEMPS methacrylate in the presence of a free radical initiator to form a crosslinked ethylene polymer composition. The crosslinking is dynamic because the disulfide bonds can be broken when the crosslinked ethylene polymer composition is subjected to a "reprocessing temperature," which is a temperature of 160°C to 230°C or 160°C to 200°C, thereby allowing the chains to move and exchange. At the reprocessing temperature, the disulfide bonds in the crosslinked ethylene polymer composition are broken to form a reprocessable ethylene polymer composition. The reprocessable ethylene composition is cooled to below the reprocessing temperature to form a re-crosslinked ethylene polymer composition.

[0102] The dynamic crosslinker BiTEMPS methacrylate enables cyclic "reprocessing" to make new polymer articles. When the crosslinked ethylene polymer composition is heated to the reprocessing temperature, the disulfide bonds are broken or otherwise cleaved, allowing the previously crosslinked ethylene polymer composition to flow at the reprocessing temperature, thereby forming a "reprocessable ethylene polymer composition". Heating to the reprocessing temperature enables chain scission and polymer chain flow, thereby allowing the ethylene composition to be easily reshaped. At the reprocessing temperature, the reprocessable ethylene polymer composition is no longer crosslinked, but is flowable, allowing the now flowable, reprocessable ethylene composition (with BiTEMPS methacrylate) to be shaped and / or manufactured into a new preform or article. When cooled to below the "reprocessing temperature", the disulfide bonds are formed again, the network is reestablished, and the re-crosslinked ethylene composition is formed in a new article configuration, returning to high viscosity (no flow at room temperature) and resistance to mechanical deformation indicating a crosslinked network. When the newly formed article of the reprocessable ethylene polymer composition is cooled to below the reprocessing temperature, the disulfide bonds in the reprocessable ethylene polymer composition are reestablished and the ethylene polymer (with BiTEMPS methacrylate) becomes a recrosslinked ethylene polymer composition in the shape of the newly manufactured article. Below the reprocessing temperature, the network disulfide bonds are stable and the recrosslinked ethylene polymer composition exhibits high viscosity and resistance to mechanical deformation indicative of the crosslinked network. This cycle of crosslinking / reprocessing / recrosslinking into a new article can be repeated.

[0103] Without being bound by a particular theory, the number of "reprocessing" cycles possible for the crosslinked ethylene compositions of the present invention can be determined by calculating the ratio of the melt viscosities of the crosslinked ethylene polymer composition before and after the reprocessing cycle (before competing thermal and oxidative permanent crosslinking occurs and prevents further reprocessing). For reprocessable, crosslinked ethylene polymer compositions, the ratio of the viscosity after reprocessing to the viscosity before reprocessing is from 0.5 to 5, or from 0.7 to 3, or from 0.9 to 2, or from 0.95 to 1.2.

[0104] Other metrics used to monitor the number of "reprocessing" cycles possible for the BiTEMPS methacrylate dynamic crosslinker before competing oxidative permanent crosslinking occurs include visual observation. The mechanically deformed formed film is heated to the reprocessing temperature and visually inspected to determine if the mechanically deformed film has healed to form a stable film.

[0105] In one embodiment, the method includes grinding the cross-linked article to form a ground material and heating the ground material to a reprocessing temperature of 180° C. to 199° C. The method includes forming the re-ground material into a reprocessable (polar) ethylene polymer composition at the reprocessing temperature, and forming the reprocessable (polar) ethylene polymer composition into a reprocessing preform at the reprocessing temperature. The method includes cooling the reprocessed preform to below the reprocessing temperature; and forming a reprocessed cross-linked article.

[0106] The reprocessed cross-linked article contains disulfide bonds formed from BiTEMPS methacrylate by the re-cross-linking reaction, and the disulfide bonds have the following structure 2.

[0107] Structure 2

[0108]

[0109] Suitable articles for reprocessing the (polar) ethylene polymer compositions (having bonds of Structure 2 formed from BiTEMPS methacrylate) include elastic films; elastic fibers; soft-touch items such as toothbrush handles and appliance handles; pads and profiles; adhesives (including hot melt adhesives and pressure sensitive adhesives); footwear (including soles and shoe insoles); automotive interior parts and profiles; foam articles (both open-cell and closed-cell foams); impact modifiers for other thermoplastic polymers such as high-density polyethylene, isotactic polypropylene or other olefin polymers; coated fabrics; hoses; pipes; weather stripping; lid linings; flooring; and combinations thereof.

[0110] In one embodiment, the method comprises heating the crosslinked article to a reprocessing temperature of 200°C to less than 250°C or 200°C to 230°C and forming the crosslinked article into a reprocessable (polar) ethylene polymer composition at the reprocessing temperature. The method comprises forming the reprocessable (polar) ethylene polymer composition into a reprocessed preform at the reprocessing temperature, cooling the reprocessed preform to below the reprocessing temperature, and forming a reprocessed thermoplastic article. The reprocessing temperature from 200°C to less than 250°C completely dissociates the disulfide bonds, thereby completely dissociating the bonds between the polymer chains in an irreversible manner. The result is a thermoplastic material.

[0111] 2. Materials

[0112] 1. Materials

[0113] The materials used in the comparative samples (CS) and the inventive examples (IE) are provided in Table 1 below.

[0114]

[0115] 2. Synthesis of BiTEMPS Methacrylate

[0116] To synthesize BiTEMPS methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (8.78 g, 39.0 mmol, provided by TCI America) was first dissolved in anhydrous petroleum ether (90 mL, provided by Sigma-Aldrich, dried over molecular sieves for 48 hours before use) and cooled to -70 °C in a dry ice / acetone bath. Afterwards, sulfur monochloride (1.30 g, 9.7 mmol, provided by Sigma-Aldrich) was dissolved in anhydrous petroleum ether (about 1.25 mL) and added dropwise to the reaction vessel over a 30-minute period. The solution was stirred at -70 °C for another 30 minutes and at room temperature for 15 minutes. Next, BiTEMPS methacrylate was precipitated by pouring the reaction solution into a large amount of distilled water and stirring at room temperature overnight. The precipitate was collected, vacuum filtered, and vacuum dried at 60 °C for 48 hours to obtain BiTEMPS methacrylate as shown in the following structure 1.

[0117] Structure 1

[0118]

[0119] 3. Preparation of crosslinkable composition (method A)

[0120] The polymer compositions (parts by weight) and process temperatures are listed in Table 2.

[0121] Table 2 - Formulations and methods for producing cross-linkable BiTEMPS compositions .

[0122]

[0123]

[0124] For each composition in Table 2, the TM 600 batch mixer (commonly known as Haake TM Batch mixer, available from PolyLabs TM ), the polymer pellets were melt blended with peroxide and BiTEMPS methacrylate in a given weight ratio at a set temperature of 30 RPM for 10 minutes. As can be seen from the table, the Haake TM The temperature in the batch mixer does not exceed 140°C to avoid unfavorable reactions. If the temperature exceeds 140°C, gel formation is observed, which is due to the Haake TMThe increased torque in the batch mixer prevented further processing of the sample. It is believed that the gel formation is the result of activation of the free radical initiator leading to crosslinking of the BiTEMPS with the vinyl polymer. At temperatures below 140°C, this activation was not observed.

[0125] After formulation, the crosslinkable polymer compositions containing the vinyl polymer, BiTEMPS, and free radical initiator (DCP) were cooled in a Carver press (cooling platens) at 20,000 psi for four minutes to produce "crosslinkable cakes" IE 1-4 for further testing.

[0126] 4. Preparation and Material Properties of Crosslinked Compositions

[0127] The cross-linkable scones were cross-linked by compression molding. For this process, cross-linkable scones IE 1-4 were placed into a Carver molding machine with a model 4095, 60 ton, dual daylight opening size 12" x 12" heating / cooling platen, and a temperature range capability of -20°C to 260°C. The Carver molding machine was capable of making 2 mm thick sheets, as well as 1 inch diameter and 0.5 inch thick buttons. For all samples, compression molding was performed at 3000 psi at 180°C for 15 minutes. The cross-linked samples were then cooled to 20°C with a cold press at 3000 psi pressure to provide cross-linked panels IE 7-9, which were submitted for further physical testing to confirm cross-linking in the samples, which are reported in Table 3 below.

[0128] Table 3. Crosslinking properties of IE 1-4 compositions

[0129]

[0130] 4. Preparation of Reprocessed Thermoplastic Articles (Method C)

[0131] After compression molding and cooling, IE 8-10 of Table 3 was reprocessed under conditions that allow reprocessing of thermoset materials into thermoplastic materials. Here, crosslinked samples IE 8-10 were cut into strips and fed into a co-rotating twin-screw Xplore MC40 micro-compounder at 50 RPM and a temperature range of 230° C. for six minutes. TM A sample of 8100 (CS1) was also reprocessed on an Xplore MC40 micro-compounder.

[0132] Table 4. Reprocessing of IE 8-10 into thermoplastic materials .

[0133]

[0134] Samples IE 11-14 were successfully extruded in a continuous manner. It was found that at temperatures above 250°C, side reactions occurred, resulting in sample degradation. Temperatures below 200°C resulted in high torque strains that inhibited extrusion. Therefore, at sufficiently high temperatures (from 200°C to 230°C), IE 11-14 can be extruded under typical polymer extrusion conditions. The strands from the extrusion were of good quality and slight surface roughness, but the physical properties were found to be similar to those of thermoplastics due to the irreversible dissociation of chemical bonds. The extruded strands of each sample IE 11-14 were collected and tested on Teflon TM The coated stainless steel plate is cooled on its surface.

[0135] Comparative Sample 1 (CS) without BiTEMPS was found to be unprocessable into thermoplastic materials. In particular for CS1, high torque within the extruder was observed at a temperature of 230°C and the product was not extrudable. Extruded materials were produced at temperatures below 200°C, however the extrudates were severely cracked and were therefore not candidates for pelletization or subsequent reprocessing.

[0136] 5. Method C: Recycling parts into thermoplastic materials

[0137] Also provided herein is the reprocessability of IE 7-9 under the conditions used to prepare thermoset materials. Here, the crosslinked plaque IE 7-9 produced above was reprocessed at a temperature of 160°C to 180°C to form a thermoset compression molded disc. As described in Table 5 below, the plaque of IE 7-9 was cut into sheets and compression molded into 1.2 inch diameter, 0.5 inch thick discs on a Carver molding machine at 160°C to 180°C for 15 minutes.

[0138] Table 5: Reprocessing of IE 7-9 into thermoset materials .

[0139]

[0140] As seen in Table 5, each of the inventive samples IE 15-17 reprocessed at temperatures between 160°C and 180°C produced a material having thermosetting properties that can be reformed into a part. Whereas the comparative sample (CS2) reprocessed at a temperature of 230°C resulted in the absence of thermosetting properties. The tensile strength of CS2 at 80°C was reduced by 80% compared to IE 15 molded at 180°C. Therefore, it was found that CS2 molded at 230°C no longer had thermosetting properties due to the irreversible cleavage of disulfide bonds.

[0141] It is particularly intended that the present disclosure is not limited to the embodiments and descriptions contained herein, but includes modifications of those embodiments including parts of the embodiments and combinations of elements of different embodiments as appear within the scope of the following claims.

Claims

1. A method, comprising: The components are fed into a mixing device, the components comprising (i) a (polar) ethylene polymer, said (polar) ethylene polymer having a melting temperature Tm, (ii) a free radical initiator having a decomposition temperature T 分解 ,and (iii) 2,2,6,6-tetramethyl-4-piperidinyl methacrylate disulfide (BiTEMPS methacrylate); mixing component (i), component (ii) and component (iii) in the mixing device at a temperature below the decomposition temperature of the free radical initiator; and A crosslinkable polymer composition is formed, the crosslinkable polymer composition comprising the (polar) vinylic polymer, the BiTEMPS methacrylate and the free radical initiator.

2. The method according to claim 1, comprising mixing at a temperature of greater than or equal to the melting temperature of the (polar) ethylene polymer and below the decomposition temperature of the free radical initiator.

3. A process according to any one of claims 1 to 2, wherein the free radical initiator is dicumyl peroxide and the process comprises mixing at a temperature below 140°C.

4. The method of claim 3, wherein the method comprises mixing at a temperature of 80°C to less than 140°C.

5. The method of any one of claims 1 to 4, comprising collecting the crosslinkable polymer composition as pellets, one or more bags, and a combination of pellets and one or more bags.

6. The method according to any one of claims 1 to 5, comprising heating the crosslinkable polymer composition to a crosslinking temperature of 160° C. to less than 199° C.; forming the cross-linkable polymer composition into a preform at the cross-linking temperature; cooling the preform to below the crosslinking temperature; as well as A cross-linked product is formed.

7. The method of claim 6, wherein the cross-linked article comprises (i) the (polar) vinyl polymer; and (ii) Bonds with structure 2 8. The method according to any one of claims 6 to 7, comprising: grinding the cross-linked article to form an abrasive material, heating the ground material to a reprocessing temperature of 180° C. to 199° C.; forming the regrind material into a reprocessable (polar) ethylene polymer composition at said reprocessing temperature; forming the reprocessable (polar) ethylene polymer composition into a reprocessable preform at the reprocessing temperature; cooling the reprocessed preform to below the reprocessing temperature; as well as A reprocessed cross-linked article is formed.

9. The method according to claim 6, comprising: heating the cross-linked article to a reprocessing temperature of 200° C. to less than 250° C.; forming the crosslinked article into a reprocessable (polar) ethylene polymer composition at the reprocessing temperature; forming the reprocessable ethylene polymer composition into a reprocessable preform at the reprocessing temperature; cooling the reprocessed preform to below the reprocessing temperature; and forming reprocessed thermoplastic articles.